Research on the Multimodal Interactive Effectiveness of College English Flipped Classroom Supported by Learning Management System —Taking “Chaoxing Learning Link” as An Example - Feng, Jing; Zhu, Xiaolan (Journal of Educational Research and Policies, 2025)
This study focuses on the university English flipped classroom teaching model supported by learning management systems, selecting the “Chaoxing Learning Tong” platform as the research object to explore its effectiveness in multimodal interaction. Through an in-depth analysis of the theory and practice of flipped classrooms, this paper reveals the functions and advantages of “Chaoxing Learning Tong” in facilitating students’ autonomous learning, teachers’ instructional management, and bidirectional interaction. Subsequently, based on case analyses, this paper provides a detailed examination of multimodal interaction examples of the learning management system in English teaching, assessing its actual effectiveness in improving learning efficiency and teaching quality. Finally, this study summarizes the advantages of interactive English teaching within this model and its significant implications for enhancing instruction, offering suggestions for the optimization of similar platforms in the future while providing theoretical and practical support for the effective implementation of flipped classrooms.